2002
DOI: 10.1103/physrevlett.89.168103
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Cross-Linked Actin Networks in Giant Vesicles

Abstract: Actin networks cross-linked by natural linkers alpha-actinin and filamin are generated in giant vesicles by polymerization through ionophore-mediated influx of Mg2+. alpha-actinin induces the formation of randomly linked networks at 25 degrees C which transform at <15 degrees C into spiderweblike gels or ringlike bundles depending on the vesicle size. Muscle filamin forms ringlike structures under all experimental conditions which can supercoil by subsequent Mg2+ addition. The polymorphism is rationalized in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
122
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 27 publications
6
122
1
1
Order By: Relevance
“…Because highly bent microtubules in very small droplets are expected to be strongly pressed against the boundary, the microtubules might rather align instead of crossing each other (39,40). Such an organization of confined filaments into rings has been observed previously for cross-linked actin filaments in liposomes (41).…”
Section: Discussionmentioning
confidence: 92%
“…Because highly bent microtubules in very small droplets are expected to be strongly pressed against the boundary, the microtubules might rather align instead of crossing each other (39,40). Such an organization of confined filaments into rings has been observed previously for cross-linked actin filaments in liposomes (41).…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, for the case of ␣-actinin, both bundle and network-like structures have been reported (28,29). This behavior would indicate that the binding energy of ␣-actinin to actin should be unusually low, so that ␣-actinin might be described by Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[3] it is found that F-actin filaments form rings with several kinks-regions with strong variation of the tangent angle to the bundle. Such kinks are not observed for actin filament rings formed by the addition of actin crosslinking proteins [9]. We demonstrate in Fig.…”
mentioning
confidence: 57%